Life-long consumption of high level of fruits and vegetables reduces tumor incidence and extends median lifespan in mice - Guo, Weimin; Ortega, Edwin F.; Wu, Dayong; Li, Lijun; Bronson, Roderick T.; Boehm, Sarah K.; Meydani, Simin Nikbin (Frontiers in Nutrition, 2023)
Objective: Epidemiological studies suggest that consumption of fruits and vegetables (FV) is negatively associated with the incidence of certain cancers and mortality. However, a causal relationship has not been demonstrated. Thus, we investigated the effect of life-long consumption of high level of FV on median lifespan, key biological functions, and pathologies in mice fed low-fat (LF) or high-fat (HF) diets and the underlying mechanisms. Methods: Using a 2 x 2 factorial design, 5-week-old male C57BL/6J mice were randomly assigned to one of four groups (n = 60/group): LF (LF-C, 10% kcal fat), HF (HF-C, 45% kcal fat) or each supplemented with 15% (w/w) of a unique FV mixture (LF+FV and HF+FV, respectively). Mice were euthanized when one group reached 50% mortality. Body weight and composition, tumor incidence, and death were monitored. Blood levels of lipids and pro-inflammatory cytokines were assessed. Results: After 21 months of feeding, HF-C group reached 50% mortality, at which time mice in all groups were terminated. HF-C had higher mortality (50.0%) compared to the LF-C group (18.3%, p = 0.0008). Notably, HF-FV had lower mortality (23.3%) compared to HF-C group (p = 0.008); there was no significant difference in mortality between HF-FV and LF-C groups. Tumors were found in all groups, and were predominantly present in the liver, followed by those of lung, intestine, and seminal vesicle. Tumor incidence in the HF-C group (73.3%) was higher than that in LF-C group (30.0%, p < 0.0001). HF+FV group had 23.3% lower tumor incidence compared to the HF-C group (p = 0.014). No significant difference in tumor incidence between the LF-C and LF+FV groups was observed. Longterm FV supplementation reduced systemic inflammation and blood lipids. Conclusions: We provide the first causal evidence that life-long intake of a diet, containing a high level and large variety of FV, decreases tumor incidence and extends median lifespan in mice fed a Western-style high-fat diet. These effects of FV are at least in part due to reduced blood levels of pro-inflammatory cytokines and improved dyslipidemia.